Diagnosis regarding the knowledge of the main social actors involved in the Geopark of the Quarta Colonia Aspirant UNESCO (Research, Society and Development, 2021)
Geopark can be defined as a form of protection and promotion of geological heritage and local sustainable development. This work aimed to make a diagnosis of the knowledge of the main social actors involved in the Geopark project of the Quarta Colônia Aspiring UNESCO, identifying aspects related to their profile, their expectations regarding the Geopark, especially regarding the potential for tourism, accommodation, leisure, crafts, and local cuisine. Entrepreneurs, artisans, people involved in tourism in the region, as well as residents and/or workers from the nine municipalities that make up the Quarta Colônia, were invited to take part in the research. Participants were provided with a link that gave direct access to an electronic questionnaire created on the Google Forms virtual platform. There was a prevalence of public servants; majority with knowledge about Geoproduct; as for the existence of guidance and tourist information, most answered not to know; there are no coherent tourist nameplates to serve tourists; there is public transport available; the presence of crafts inspired by the local landscape; food services with an emphasis on regional cuisine; rural and urban accommodation available; several leisure proposals. With this work, it became even more evident how much the region of the Fourth Colony of Italian immigration is prepared to become a Geopark.